The return of Keynes and the Phillips curve in Latin America: evidence from four countries. (January 2020) - Caldentey, Esteban Pérez; Perry, Nathan; Vernengo, Matías
Abstract : Robert Rowthorn, in his Godley–Tobin Lecture, suggests that Keynesian policies have again been incorporated by the mainstream of the profession, and the old Phillips relation is again relevant. In other words, there seems to be a persistent trade-off between inflation, wage inflation in particular, and unemployment rates, properly measured, which would create the space for Keynesian policies. This paper discusses the return of Keynesian economics, in particular in Latin American economies. While it is true that Keynesian economics made a comeback in terms of policy in Latin America, as in other parts of the world, in the aftermath of the global financial crisis of 2008–2009, it is also true that the Keynesian moment was relatively weak and short-lived. The evidence in Latin America for a Phillips curve is relatively weak, and suggests that inflation is often cost-push rather than demand-pull, which could be understood to suggest that there is space for expansionary fiscal policy, at least in the absence of an external constraint. The authors remain skeptical about the return of Keynesian economics at the theoretical level, and the possibilities for Keynesian policies in the region.